Analysis Of Accounting Information System Output Based On Consistency Of Financial Report Presentation - Ratu Munawarah; Ratih Kusumastuti; Achmad Hizazi (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the quality of Accounting Information Systems (AIS) output by focusing on the consistency of financial statement presentation as a key indicator of the reliability of accounting information. Consistency of presentation is an important principle in financial reporting because it allows report users to conduct comparative performance evaluations from period to period. However, in many organizations, especially medium-sized companies and trading companies, variations in formats, account classifications, and differences in recording methods are still found, which affect the comparability of reports. This study uses secondary data in the form of annual financial statements of trading companies that have been published publicly for three consecutive years. The analysis is conducted by assessing the conformity between presentation standards for each period, the stability of the use of accounting methods, and the uniformity of account classifications produced by the AIS. The results of this study indicate that the consistency of financial statement presentation is largely determined by the quality of the AIS design, the company's level of compliance with accounting standards, and the effectiveness of the data input process. Several companies demonstrated a high level of consistency, characterized by similarities in report structure and measurement methods across periods. Conversely, companies that experienced changes in report formats and variations in account classifications showed that their AIS output was not optimal in maintaining report comparability. These findings indicate the importance of improving the input process by system users, strengthening internal control procedures, and updating the system to ensure that the AIS is capable of producing reliable and consistent financial reports. This study provides a practical contribution to companies in evaluating AIS performance and serves as a basis for recommendations to improve the quality of financial reporting in the future.